High risky behaviors among intravenous drug users in Isfahan, Iran: A study for hepatitis C harm reduction programs - Hassannejad, Razieh (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Intravenous drug users (IVDUs) who share needles/syringes and practice sexual behaviors, are the most important group in the transmission of blood-borne infection diseases such as hepatitis C virus (HCV). Therefore identification of prevalent high-risky behaviors among IVDUs to detect the most route of transmission among them is essential to develop harm reduction programs among IVDUs and decrease HCV transmission from them to community. METHODS: The cross-sectional study was carried out on 1510 intravenous drug users from November 2008 to February 2009 in Isfahan province, Iran. After obtaining consent form from participants, information was collected by interviewer-administered validated questionnaire. The data was analyzed with descriptive statistical methods by SPSS software, version 15. RESULTS: 1510 IVDUs participated in the study with the mean age 32.16 ± 8.26. 66.4% of participants had a history of illegal sexual activity. Among male IVDUs who had illegal sexual contact, 40.6% reported having homosexual contact and 36.2% of them have used condom in their contact. Also 57.7% had sexual contact with female sex workers. 83.5% of IVDUs reported having multiple sexual partners, and 30.9% had IVDUs sexual partners. The mean number of injection and duration of injection among IVDUs were 75.12 ± 95.51 times per month and 12.34 ± 7.53 years respectively. 36.9% of subjects have reported sharing needles/syringes. CONCLUSIONS: According to the high prevalence of unprotected sexual contacts and unsafe injection among IVDUs, effectiveness interventions and harm reduction programs are necessary to prevent spread of blood-borne infection diseases particularly HCV. With reduction of risky behaviors and consequently decrease of spread of HCV, these programs benefit both drug users and society.